America’s grasslands: the future of grasslands in a changing landscape - (:unkn) unknown (National Wildlife Federation and Kansas State University, 2014)
At the second America’s Grasslands Conference, we grappled with this issue of loss of grasslands (especially since USDA does not measure the lost of grasslands in a formal fashion). We also explored and discussed other critical issues including how to raise the profile of grasslands, what federal policy opportunities exist to conserve grasslands, and importantly, how conservationists and private landowners (mostly ranchers) can better work together to conserve grasslands. The focus on working with ranchers was an important one. There was a high level of energy and enthusiasm around this issue, and participants (especially researchers) were particularly excited by the opportunity to have conversations with ranchers and other private landowners about ways to work together to conserve grasslands.
Keywords: Grasslands; Conservation; Ranchers; Federal policy; Ecosystems